Remittances and Household Welfare: A Case Study of Bangladesh - Selim Raihan; Bazlul H. Khondker; Guntur Sugiyarto; Shikha Jha (Asian Development Bank (ADB), 2009)
This paper examines the impacts of international remittances on household consumption expenditure and poverty in Bangladesh using computable general equilibrium modeling of the Bangladesh economy and microeconometric analysis at the household level. The former assesses the economic effects and distributional implications of remittances at the macro, sectoral, and household group levels, while the latter shows the association between remittances and household consumption expenditure, including poverty status. The first results show that remittances have positive effects on the economy and reduce poverty. It is estimated that 1.7 out of the 9 percentage point reduction in the headcount ratio during 2000–2005 was due to the growth in remittances. A closer look at the household level further reveals the positive and significant impacts of remittances on the household's food and housing-related expenditures. The impacts on education and health expenditures are also positive but insignificant. Moreover, the logit regression results suggest that the probability of the household becoming poor decreases by 5.9% if it receives remittances, which further confirms the positive impact of remittances. Given that migration and remittances also bring costs to the society, the study findings call for policies to maximize their benefits. This includes attracting more remittances through formal channels and increasing their productive use.
hdl:11540/1840
Keywords: 330; International migration and remittances; Household welfare; Poverty; CGE Model; Microeconometrics; Bangladesh